Krystiana Lupy teatr transparentny (uwagi o funkcjach przezroczystości w scenografii teatralnej) - Gołos-Dąbrowska, Katarzyna (Załącznik Kulturoznawczy, 2019)
The article is an attempt to describe some of the most important transparent constructions in Krystian Lupa’s theatre and to explain their functions. In the text, I focused on the main and most frequently repeated transparent elements of the scenography; prisms (which fulfil the role of internal frames), transparent walls (places where actors are peeping over), and bars and grids which suggest closing some space off or isolating the actors.